Effects of sodium and potassium on fusion characteristics of petroleum coke ash with high vanadium and nickel. (1st February 2022) - Li, Jiazhou; Chen, Xiaodong; Wang, Bing; Zhang, Wei; Zhang, Yuming; Guo, Jinjun; Zhang, Wenbin; Ge, Zhihong; Sun, Qiang
Highlights: The effects of Na and K on petcoke ash fusibility are studied at reducing atmosphere. The mineral evolutions of ash at high temperatures contribute to the change of AFT. The mixed alkaline effect can influence the AFT variations markedly. Abstract: Ash fusion temperatures (AFTs) are widely employed to evaluate petroleum coke ash fusibility, which has significant effects on its high-value and clean utilization. Sodium (Na) and potassium (K) both are considered to be the effective components to improve the ash fusion characteristics for slag tapping of entrained flow gasifiers. Herein, the effects of (Na2 O + K2 O) and Na2 O/K2 O mass ratio on the fusion behaviors of petroleum coke ash with high vanadium (V) and nickel (Ni) were investigated by AFTs tests in conjunction with X-ray diffraction and thermodynamic equilibrium calculations. The results demonstrated that AFTs followed a significant decline with the increase in (Na2 O + K2 O) content. Vanadium trioxide (V2 O3 ), coulsonite (FeV2 O4 ), nickel (Ni) and nepheline ((Na, K)AlSiO4 ) were the dominant crystalline minerals formed in high-temperature ash. The formation of low-melting (Na, K)AlSiO4 was responsible for the variation in AFTs because of the low ionic potential of Na + and K + . AFTs dropped slightly as the Na2 O/K2 O mass ratio decreased from 10/0 to 4/6, and then exhibited a sharp rise. The mixed alkaline effect between Na and K effectively influenced the AFTs variations. When the Na2 O/K2 O mass ratio was higher than 8/2, Na existed in eutectics or amorphous matters rather than Na-bearing crystalline species at high temperatures. As the Na2 O/K2 O mass ratio further decreased, the crystalline phase (Na, K)AlSiO4 was converted into high-melting leucite (KAlSi2 O6 ), which resulted in the sharp increase in AFTs.